Design and implementation of control of perching mechanism - Quek, Jian Xing. (2013)
Unmanned Aerial Vehicles (UAVs) are aerial vehicles that operate without the need of any human pilot on board. As its popularity to be used in military and civilian domains for various applications are increasing these days, people would prefer a UAV that has a long lasting battery life, thus the need to increase the UAV operation life by different approach.